Preparation method and application of FeSiCr alloy wave-absorbing powder with high length-diameter ratio
By performing rugby shape pretreatment and ball milling process optimization on FeSiCr alloy wave absorbing powder, a sheet-shaped FeSiCr alloy wave absorbing powder with an aspect ratio of up to 120 was prepared, which solved the problem of insufficient powder length and diameter ratio and easy to break in the prior art, and significantly improved the wave absorbing performance.
Patent Information
- Application Number
- CN202510085370.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The application of existing FeSiCr alloy wave absorbing powder in the low frequency band is difficult, and the length and diameter of the sheet powder prepared by ball mill is relatively low and easy to break.
By pretreating the spherical FeSiCr granule powder in rugby shape and ball milling with zirconia milling balls in an alumina ball milling tank, combining anhydrous ethanol and oleic acid as dispersant and ball milling additives, a sheet-like FeSiCr alloy absorbing powder with a high aspect ratio was prepared.
The high aspect ratio of FeSiCr alloy wave absorbing powder is achieved, reaching 120, which improves the magnetic permeability and flaking degree, avoids particle edge cracks and fractures, and significantly improves the wave absorbing performance.
Smart Images

Figure CN119897457A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of absorbing stealth materials, and specifically relates to a preparation method and application of a FeSiCr alloy absorbing powder with a high aspect ratio. Background Art
[0002] With the development of electronic technology, especially the popularization of mobile communications and computers, our living environment has been increasingly polluted by electromagnetic radiation. In recent years, electromagnetic interference and electromagnetic pollution induced by electromagnetic radiation from wireless communications have become increasingly apparent, seriously affecting the urban environment and threatening human health. This situation has put forward new requirements for low-frequency absorbing materials. In view of the requirements for electromagnetic absorption in the microwave band, FeSiCr alloy powder has the characteristics of high real and imaginary parts of complex magnetic permeability and high loss tangent value, which can meet the requirements of wave absorption.
[0003] However, due to the existence of the Snoek limit, the complex magnetic permeability of FeSiCr alloy absorbing powder will decrease with the increase of frequency, so its application in the low frequency band is still very difficult. Flaked FeSiCr alloy absorbing powder has the characteristics of high shape factor, high saturation magnetization, low coercive force and low magnetocrystalline anisotropy. Flaking refers to the process of treating solid particles into thin flakes by physical or chemical methods. Flaking FeSiCr alloy absorbing powder can break through the Snoek limit. Flaked powder has a higher aspect ratio and improved shape anisotropy, which effectively improves the complex magnetic permeability of the powder. At the same time, when the thickness of the flaky particles is less than the skin depth of the frequency band, it can also effectively suppress the eddy current effect and avoid surface reflection. Therefore, the flaking treatment of FeSiCr is a very effective and important way to optimize and regulate its performance.
[0004] At present, the most common method for flaking FeSiCr alloy absorbing powder is ball milling, which is divided into wet ball milling and dry ball milling. Compared with dry ball milling, wet ball milling has the advantages of high efficiency, uniform particles, low oxidation degree and low agglomeration. However, due to the brittleness of FeSiCr alloy itself, if stainless steel tanks and stainless steel grinding balls are used for ball milling, FeSiCr alloy absorbing powder is very easy to break. The edges of the particles prepared by ball milling will have cracks and then break easily, and the obtained flaky powder cannot obtain a high aspect ratio. Therefore, it is particularly important to find a suitable process to prepare flaked FeSiCr alloy absorbing powder with a large aspect ratio. Summary of the invention
[0005] In view of the above-mentioned problems or shortcomings, and in order to solve the problem of relatively insufficient aspect ratio of existing FeSiCr alloy absorbing powder flaky products, the present invention provides a method for preparing and applying a high aspect ratio FeSiCr alloy absorbing powder. The aspect ratio of the flaky FeSiCr alloy absorbing powder prepared by the present invention is as high as 120, the degree of flaking is very high, and it has a high magnetic permeability. At the same time, the prepared high aspect ratio FeSiCr alloy absorbing powder accounts for a high proportion.
[0006] In order to achieve the purpose of the present invention, the specific technical solution of the present invention is as follows:
[0007] A method for preparing FeSiCr alloy microwave absorbing powder with high aspect ratio comprises the following steps:
[0008] Step 1: pre-treat the spherical FeSiCr particle powder into a rugby ball shape.
[0009] Step 2, adding grinding balls, dispersants and ball milling aids to the FeSiCr football-shaped powder pretreated in step 1 to perform ball milling to obtain flaky FeSiCr particles;
[0010] Step 3: The flaky FeSiCr particles obtained in step 2 are washed, dried and sieved in sequence to obtain FeSiCr alloy microwave absorbing powder with a high aspect ratio.
[0011] Furthermore, the inner lining material of the ball mill is alumina, which reduces the problem of hard lining materials such as stainless steel tanks and FeSiCr alloy absorbing powder being easily broken due to hard collision, resulting in cracks on the edges of particles after ball milling and easy breakage, improves the intensity of hard collision of powders during ball milling, and obtains flaky FeSiCr alloy absorbing powder with a higher aspect ratio.
[0012] Furthermore, the grinding balls are made of zirconium oxide, which reduces the problem of stainless steel grinding balls and FeSiCr alloy absorbing powder being easily broken due to hard collision, resulting in cracks on the edges of particles after ball milling and easy breakage, improves the intensity of hard collision of powders during ball milling, and obtains flaky FeSiCr alloy absorbing powder with a higher aspect ratio.
[0013] Furthermore, the dispersant is anhydrous ethanol, and the ball milling aid is oleic acid.
[0014] Furthermore, the spherical FeSiCr particles include 88-90 wt. % Fe, 4.5-5.5 wt. % Si and the balance is Cr.
[0015] Furthermore, the particle size of the spherical FeSiCr particles is 10-20 μm; and the diameter of the grinding balls is 5-8 mm.
[0016] Furthermore, the mass ratio of the FeSiCr particle raw material, the dispersant and the grinding ball is 1:1-1.4:4-8.
[0017] Furthermore, the ball mill has a rotation speed of 20 to 40 Hz and a time of 12 to 18 hours.
[0018] Furthermore, the aperture of the sieve used for the screening is 100 to 600 meshes.
[0019] Furthermore, the high aspect ratio FeSiCr alloy absorbing powder prepared by the above method is used as a absorbing material in the low frequency band.
[0020] The present invention pre-treats spherical FeSiCr particle powder into a rugby shape, and then prepares a flaky FeSiCr alloy absorbing powder by ball milling; this is because the rugby shape is closer to the flaky shape, and the intensity of the collision of spherical particles during the ball milling process is greatly reduced, thereby improving the problem of cracks on the edges of the particles after ball milling, which is easy to break and eventually leads to a low aspect ratio of the flaky particles. A ball milling process using an alumina ball mill and a zirconium oxide grinding ball is further provided to further weaken the intensity of the collision during the ball milling process, and finally prepare a FeSiCr absorbing powder with an aspect ratio of up to 120. The process of the present invention is simple, and the prepared flaky powder has smooth edges and surfaces, regular shapes, and excellent performance of the FeSiCr absorbing powder. Furthermore, the dispersant in the present invention is anhydrous ethanol, and the ball milling aid is oleic acid, which does not involve toxic and harmful chemicals and is environmentally friendly.
[0021] In summary, the present invention prepares FeSiCr absorbing powder with high aspect ratio and good lamellarity, which has more surface active sites and can be effectively combined with other high-resistance materials by chemical or physical methods to reduce the dielectric constant. By controlling the thickness of the outer layer medium, the dielectric constant is reduced without affecting the magnetic permeability, which can promote impedance matching and optimize its absorbing performance. It has important practical application value and broad application prospects in the field of electromagnetic wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The XRD test results of the FeSiCr alloy powder obtained in Example 3;
[0023] Figure 2 is a SEM image of the FeSiCr alloy powder with a high aspect ratio obtained in Example 3;
[0024] Figure 3 is a graph of aspect ratios of Examples 1-6;
[0025] Figure 4 These are the electromagnetic parameter test results of Examples 1-6. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0027] A method for preparing FeSiCr alloy microwave absorbing powder with high aspect ratio comprises the following steps:
[0028] Step 1: pre-treat the spherical FeSiCr particle powder into a rugby ball shape.
[0029] Step 2: Place the FeSiCr rugby ball-shaped powder obtained in step 1 in a ball mill, add grinding balls, dispersants and ball milling aids, and perform ball milling to obtain flaky FeSiCr particles; the inner lining material of the ball mill is alumina, and the capacity is 30L; the material of the grinding balls is zirconium oxide.
[0030] Step 3: The flaky FeSiCr particles obtained in step 2 are washed, dried and sieved in sequence to obtain FeSiCr alloy absorbing powder with an aspect ratio of up to 120.
[0031] The raw material components of FeSiCr particles in the embodiment are 88-90wt.% Fe, 4.5-5.5wt.% Si, and the balance is Cr. The particle size of the FeSiCr particle raw material is 10-20μm, and the diameter of the grinding ball is 5-8mm. The dispersant is preferably anhydrous ethanol, and the ball milling aid is oleic acid. The mass ratio of FeSiCr particle raw material, dispersant and grinding ball is 1:1-1.4:4-8, and the mass of the ball milling aid is 30g. The speed of the ball mill is 20-40Hz; the time is 12-18h. The cleaning solvent is anhydrous ethanol; the drying temperature is 60°C, and the time is 8h. After obtaining the flaky FeSiCr particles, the flaky FeSiCr particles obtained in the embodiment are sieved with a sieve aperture of 200-600 mesh.
[0032] Example 1
[0033] 10 kg of spherical FeSiCr particles were pretreated into a rugby shape and then loaded into a ball mill barrel. 30 kg of zirconia grinding balls with a particle size of 5 mm were added to the ball mill barrel. 5 kg of anhydrous ethanol and 30 g of oleic acid were added, and the ball milling rate was set to 30 Hz for 12 hours. After the ball milling, the raw materials were taken out, the powder was washed three times with anhydrous ethanol, and then dried at 60° C. for 8 hours to obtain 10 kg of flaky FeSiCr particles. Three groups of 50 g of the above flaky FeSiCr particles were taken out for sieving treatment, and the sieving vibration machine was set with 200 mesh screen, 300 mesh screen, 400 mesh screen, 500 mesh screen and 600 mesh screen from top to bottom. After the three groups were sifted, 30.2 g, 30.8 g and 29.6 g of FeSiCr alloy powder with a high aspect ratio were obtained respectively.
[0034] Example 2
[0035] 7.5 kg of spherical FeSiCr particles were pretreated into a rugby shape and then loaded into a ball mill barrel. 30 kg of zirconia grinding balls with a particle size of 5 mm were added to the ball mill barrel. 5 kg of anhydrous ethanol and 30 g of oleic acid were added, and the ball milling rate was set to 30 Hz for 12 hours. After the ball milling, the raw materials were taken out, and the powder was washed three times with anhydrous ethanol, and then dried at 60° C. for 8 hours to obtain 7.5 kg of flaky FeSiCr particles. Three groups of 50 g of the above flaky FeSiCr particles were taken out for sieving treatment, and the sieving vibration machine was set with 200 mesh screen, 300 mesh screen, 400 mesh screen, 500 mesh screen and 600 mesh screen from top to bottom. After the three groups were sifted, 35.2 g, 33.8 g and 34.6 g of FeSiCr alloy powder with a high aspect ratio were obtained, respectively.
[0036] Example 3
[0037] 5 kg of spherical FeSiCr particles were pretreated into a rugby shape and then loaded into a ball mill barrel. 30 kg of zirconia grinding balls with a particle size of 5 mm were added to the ball mill barrel. 5 kg of anhydrous ethanol and 30 g of oleic acid were added, and the ball milling rate was set to 40 Hz for 12 hours. After the ball milling, the raw materials were taken out, and the powder was washed three times with anhydrous ethanol, and then dried at 60° C. for 8 hours to obtain 5 kg of flaky FeSiCr particles. Three groups of 50 g of the above flaky FeSiCr particles were taken out for screening treatment, and the screening vibration machine was set with 200 mesh screen, 300 mesh screen, 400 mesh screen, 500 mesh screen and 600 mesh screen from top to bottom. After the three groups were screened, 38.1 g, 37.7 g and 38.6 g of FeSiCr alloy powder with a high aspect ratio were obtained, respectively.
[0038] Example 4
[0039] 5 kg of spherical FeSiCr particles were pretreated into a rugby shape and then loaded into a ball mill barrel. 30 kg of zirconia grinding balls with a particle size of 5 mm were added to the ball mill barrel. 5 kg of anhydrous ethanol and 30 g of oleic acid were added, and the ball milling rate was set to 40 Hz for 14 hours. After the ball milling, the raw materials were taken out, the powder was washed three times with anhydrous ethanol, and then dried at 60° C. for 8 hours to obtain 5 kg of flaky FeSiCr particles. Three groups of 50 g of the above flaky FeSiCr particles were taken out for sieving treatment, and the sieving vibration machine was set with 200 mesh screen, 300 mesh screen, 400 mesh screen, 500 mesh screen and 600 mesh screen from top to bottom. After the three groups were sifted, 40.2 g, 41.8 g and 41.6 g of FeSiCr alloy powder with a high aspect ratio were obtained respectively.
[0040] Example 5
[0041] 5 kg of spherical FeSiCr particles were pretreated into a rugby shape and then loaded into a ball mill barrel. 30 kg of zirconia grinding balls with a particle size of 5 mm were added to the ball mill barrel. 5 kg of anhydrous ethanol and 30 g of oleic acid were added, and the ball milling rate was set to 40 Hz for 16 hours. After the ball milling, the raw materials were taken out, and the powder was washed three times with anhydrous ethanol, and then dried at 60° C. for 8 hours to obtain 5 kg of flaky FeSiCr particles. Three groups of 50 g of the above flaky FeSiCr particles were taken out for screening, and the screening vibration machine was set with 200 mesh screen, 300 mesh screen, 400 mesh screen, 500 mesh screen and 600 mesh screen from top to bottom. After the three groups were screened, 43.2 g, 42.1 g and 42.9 g of FeSiCr alloy powder with a high aspect ratio were obtained, respectively.
[0042] Example 6
[0043] 5 kg of spherical FeSiCr particles were pretreated into a rugby shape and then loaded into a ball mill barrel. 30 kg of zirconia grinding balls with a particle size of 5 mm were added to the ball mill barrel. 5 kg of anhydrous ethanol and 30 g of oleic acid were added, and the ball milling rate was set to 40 Hz for 18 hours. After the ball milling, the raw materials were taken out, and the powder was washed three times with anhydrous ethanol, and then dried at 60° C. for 8 hours to obtain 5 kg of flaky FeSiCr particles. Three groups of 50 g of the above flaky FeSiCr particles were taken out for screening treatment, and the screening vibration machine was set with 200 mesh screen, 300 mesh screen, 400 mesh screen, 500 mesh screen and 600 mesh screen from top to bottom. After the three groups were screened, 40.2 g, 391 g and 38.9 g of FeSiCr alloy powder with a high aspect ratio were obtained, respectively.
[0044] Figure 1 This is the XRD test result of the flaky FeSiCr alloy powder obtained in Example 3. It can be seen from the figure that after 12 hours of ball milling, the three main peaks are still near 44.8°, 65.3°, and 82.6°, the peak intensity is reduced, the half-peak width is widened, the main phase is α-Fe(Si,Cr), and no phase change occurs, and the oxides of the three elements are not generated.
[0045] Figure 2 This is a SEM image of the flaky FeSiCr alloy powder with a high aspect ratio prepared in Example 3. As can be seen from the figure, the remaining particles after the screening process are all large flaky particles with a relatively flat surface, smooth overall, and almost no cracks.
[0046] Figure 3The figure is the aspect ratio diagram of Examples 1-6. It can be seen from the figure that, under the condition of unchanged process, the less the amount of FeSiCr particles, the larger the aspect ratio of the powder obtained by ball milling after screening. The aspect ratio of the powder obtained in Example 3 is the largest, up to 120. However, as the ball milling time increases, the powder will be more broken and the aspect ratio will decrease.
[0047] It can be seen from the above embodiments that the present invention pre-treats the spherical FeSiCr particle powder into a rugby shape, and then uses ball milling to prepare a flaky FeSiCr alloy absorbing powder; the present invention utilizes the rugby shape to be closer to a flaky shape, and the intensity of the collision of spherical particles during the ball milling process is greatly reduced, thereby improving the problem of cracks on the edges of the particles after ball milling, which is easy to break and eventually leads to a low aspect ratio of the flaky particles. A ball milling process using an alumina ball mill and a zirconia grinding ball is further provided to further weaken the intensity of the collision during the ball milling process, and finally prepare a FeSiCr absorbing powder with an aspect ratio of up to 120. The present invention has a simple process, and the prepared flaky powder has smooth edges and surfaces, regular morphology, and excellent performance of the FeSiCr absorbing powder.
Claims
1. A method for preparing FeSiCr alloy microwave absorbing powder with high aspect ratio, characterized in that: The following steps are involved: Step 1, pre-treating the spherical FeSiCr particle powder into a rugby shape; Step 2, adding grinding balls, dispersants and ball milling aids to the FeSiCr rugby ball-shaped powder obtained in step 1, and performing ball milling to obtain flaky FeSiCr particles; Step 3: The flaky FeSiCr particles obtained in step 2 are washed, dried and sieved in sequence to obtain FeSiCr alloy microwave absorbing powder with a high aspect ratio.
2. The method for preparing the high aspect ratio FeSiCr alloy absorbing powder according to claim 1, characterized in that: The inner lining material of the ball mill is alumina.
3. The method for preparing the FeSiCr alloy microwave absorbing powder with high aspect ratio as claimed in claim 1, characterized in that: The material of the grinding balls is zirconium oxide.
4. The method for preparing the high aspect ratio FeSiCr alloy absorbing powder according to claim 1, characterized in that: The dispersant is anhydrous ethanol, and the ball milling aid is oleic acid.
5. The method for preparing the FeSiCr alloy microwave absorbing powder with high aspect ratio as claimed in claim 1, characterized in that: The spherical FeSiCr particles include 88-90 wt. % Fe, 4.5-5.5 wt. % Si and the balance is Cr.
6. The method for preparing the high aspect ratio FeSiCr alloy microwave absorbing powder according to claim 1, characterized in that: The particle size of the spherical FeSiCr particles is 10-20 μm, and the diameter of the grinding balls is 5-8 mm.
7. The method for preparing the FeSiCr alloy microwave absorbing powder with high aspect ratio as claimed in claim 1, characterized in that: The mass ratio of the FeSiCr particles, the dispersant and the grinding balls is 1:1-1.4:4-8.
8. The method for preparing the FeSiCr alloy microwave absorbing powder with high aspect ratio as claimed in claim 1, characterized in that: The ball milling speed is 20-40 Hz, and the time is 12-18 hours.
9. The method for preparing the FeSiCr alloy microwave absorbing powder with high aspect ratio as claimed in claim 1, characterized in that: The aperture of the sieve used for the screening is 100 to 600 meshes.
10. The method for preparing the FeSiCr alloy microwave absorbing powder with high aspect ratio as claimed in claim 1, characterized in that: The FeSiCr alloy absorbing powder with high aspect ratio is used as absorbing material in low frequency band.